DIABETES IN POLAND: EPIDEMIOLOGY, MORTALITY AND DIAGNOSTICS - Illia Koval; Klaudia Romejko; Barbara Kujawa; Sandra Sienkiewicz; Jagoda Saniuk; Justyna Rajczyk; Aleksandra Oparcik; Kacper Wojtala; Weronika Kielińska; Małgorzata Golik; Anna Popowicz; Michał Dorota; et al. (International Journal of Innovative Technologies in Social Science, 2025)
This paper presents current knowledge on diabetes mellitus (ICD-10 E10-E14) and its clinical impact. Diabetes is a growing global problem, with over 3 million adults affected in Poland alone. The disease develops as type 1, caused by autoimmune destruction of pancreatic β-cells, or as type 2, driven mainly by insulin resistance and obesity. Both forms lead to impaired glucose uptake and abnormal fat and protein metabolism. Common symptoms include thirst, polyuria, fatigue, weight loss, and recurrent infections, though type 2 diabetes often remains silent for years. Persistent hyperglycemia promotes toxic metabolite accumulation, microangiopathy, neuropathy, and multiorgan complications. Cardiovascular manifestations, such as diabetic cardiomyopathy and arrhythmias, significantly increase morbidity and mortality. Early detection, lifestyle modification, and improved diagnostic strategies remain essential to reduce the burden of disease.